Keadilan Administratif dalam Sistem Distribusi Bantuan Sosial Berbasis Algoritma: Studi tentang Transparansi Digital dalam Layanan Publik di Indonesia - Sarjito, Aris; Djati, Sundring Pantja (Universitas 17 Agustus 1945 Surabaya, 2025)
This study investigates the concept of administrative justice within algorithm-based decision systems used in distributing social assistance programs in Indonesia. The research aims to evaluate the extent to which digital transparency is upheld in these automated public service mechanisms. Employing a qualitative approach based on secondary data, the study analyses policy documents, regulatory frameworks, technical algorithm manuals, government reports, and investigative journalism from multiple regions. Data were examined through qualitative content analysis. The findings indicate that algorithmic opacity, limited public communication regarding eligibility criteria, and weak regulatory oversight hinder the realization of administrative justice. This article makes a significant contribution to public administration literature by integrating the ethical and administrative dimensions into the study of algorithmic governance. It offers a critical assessment of digital governance practices in an emerging economy and advocates for the ethical implementation of algorithms in the public sector.